Analisis Perbandingan Harga Satuan Galian Tanah Mekanis Menggunakan Permen-PUPR Tahun 2022 Dan 2016 - Setiyo Ferdi Yanuar; Nanang Saiful Rizal; Taufan Abadi (HEXAGON, 2022)
Work Unit Price Analysis or commonly referred to as AHSP calculation of the cost of labor, materials and equipment to get the unit price for a certain type of work. Over time, the coefficient on the AHSP has changed. This is because the world of construction is always experiencing developments in the technology applied. This development can include in terms of materials, work aids, and technology used in heavy equipment used to assist work in the world of civil engineering.The last regulation used in the calculation of AHSP is PERMEN-PUPR no. 28 of 2016. On January 5, 2022, PERMEN-PUPR no. 1 of 2022 was stipulated as a substitute for the basis for calculating AHSP. In the new regulation, many coefficients have been changed both in terms of labor, materials, and tools. With the change in the coefficient in the new regulation, it makes the price of mechanical earth excavation cheaper, which makes construction players complain about this. So it is necessary to do an analyst to compare the unit price with direct costs in the field.Based on the results of calculations and observations, the unit price for mechanical earth excavation based on the 2016 PERMEN is Rp. 22,465.00, based on the 2022 PERMEN is Rp. 11,314.00, while based on direct observations in the field, the direct costs incurred are Rp. 8,042.00.